Effect of Different Protein Levels on Arabi Chicken Performance - Al-Khalifa , H.; Al-Nasser, A. (International Journal of Poultry Science, 2012)
It is important to note that feeding cost can reach up to 60-75% of the total farm production cost. This study investigated some feeding management practices needed by the Arabi chickens during the brooding phase. Three different feed rations were fed to Arabi chickens and the effect of these feed rations on the performance was evaluated. These feed rations contained three different levels of dietary protein: 18, 21 and 22%. Variables measured included body weight feed consumption and feed efficiency. Results showed that there was no significantly different protein levels indicating that using a diet with 18% protein level is as satisfactory as those with 21 and 22%. Therefore, a lower protein level can be possibly fed reducing the cost of feed. In conclusion, feeding a diet treatment with 18% protein is recommended for the Arabi chickens.